Strategic supplementation of crossbred steers fed forages from cereal-legume cropping systems with cowpea hay - Umunna, N.N.; Osuji, P.O.; Nsahlai, I.V. (Informa UK Limited, 1997)
Forty-four crossbred steers were used in a 252-day trial to assess the feeding value of forages from two cereal-legume cropping systems Cropping system 1 comprised oat-vetch (Avena sativa-Vicia dasycarpa), wheat-trifolium (Triticum aestivum-Trifolium steudneri), teff (Eragrostis tef) and cowpea )Vigna unguiculata). Cropping system 2 had maize-lablab (Zea mays-Lablab purpureus) instead of wheat-trifolium. Treatments comprised ad libitum teff straw alone (T1), teff straw plus wheat middlings (T2), forages from cropping system 1 fed in the order and length (days) oat-vetch (112), wheat-trifolium plus cowpea hay (70) and teff straw plus cowpea hay (70) (T3) or forages from cropping system 2 fed in the same order and length (days) (T4). Cowpea hay and wheat middlings were supplemnted at 1 percent of body weight. Maize-lablab and oats-vetch forages contained similar levels of CP which were higher than that in wheat-trifolium. The basal teff straw did not meet the calcium (Ca) and phosphrous (P) needs of the steers (T1). However, supplementation with cowpea hay satisfied all mineral needs and improved DM disappearance (P<0.01) from nylon bags. Steers on T2 gained more (P<0.01) live weight and were more (P<0.01) efficient than steers on T4 (541 vs 373; 0.10 vs 0.08) which in turn were superior (P<0.05) to those on T3 kg/hd/day) resulting to similar growth rate (200 vs 234 g/day) between T3 and T4, the intake of wheat-trifolium plus cowpea hay (T3) was 5 percent higher than that of maize-lablab plus cowpea hay. However, the superior digestibility of maize-lablab plus cowpea hay resulted in 1.1 times increased digestible organic matter intake which could explain the superior growth rate of T4 steers (411 vs 283). The inferior feeding value of forages from cropping system 1 (T3) could be attributed to leaf shattering of the trifolium component. It was concluded that the intercropped feeds were still deficient in CP and energy and should not be used as sole feed.